THE EFFECT OF MOTIVATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE AT THE YOUTH, SPORTS AND TOURISM SERVICE OF PASER DISTRICT - Rachmad Ajends Ariansyah; Meiske Claudia; Tinik Sugiati (ADISAM Publisher, 2025)
The purpose of this research is to analyze the influence of motivation, work discipline on employee job satisfaction, the influence of motivation, work discipline on employee performance and the influence of job satisfaction, motivation, work discipline on employee performance through employee job satisfaction at the Paser Regency Youth, Sports and Tourism Service. The type of research used in this research is quantitative research with an associative approach that explains cause and effect relationships. The population in this study were all civil servants who worked at the Paser Regency Youth, Sports and Tourism Service, totaling 30 people. In this study, total sampling or census techniques were used because the number of samples was the same as the population, so the number of samples in this study was 30 people. In this research, the data obtained was primary data, namely the collection was carried out using a questionnaire that had been provided, while secondary data was carried out by looking at documents at the relevant agencies according to the researcher's data needs. The analysis technique used in this research is path analysis. The results of the data analysis explain that motivation and job satisfaction have a positive and significant effect on the performance of ASN employees of the Paser Regency Youth, Sports and Tourism Service, work discipline has no effect on the performance of ASN employees of the Paser Regency Youth, Sports and Tourism Service. Motivation and work discipline have a positive and significant effect on job satisfaction of ASN employees at the Paser District Youth, Sports and Tourism Service. Motivation and work discipline have a positive and significant effect on performance through job satisfaction of ASN employees at the Paser District Youth, Sports and Tourism Service.